2019
DOI: 10.1016/j.mito.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Multichromosomal structure of the onion mitochondrial genome and a transcript analysis

Abstract: The structures of plant mitochondrial genomes are more complex than those of animals. One of the reasons for this is that plant mitochondrial genomes typically have many long and short repeated sequences and intra- and intermolecular recombination may create various DNA molecules in this organelle. Recombination may sometimes create a novel gene that causes cytoplasmic male sterility (CMS). The onion has several cytoplasm types, with some causing CMS while others do not. The complete mitochondrial genome seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 27 publications
3
20
0
Order By: Relevance
“…Because of the highly dynamic structure of mitochondrial genomes of angiosperms, alignments of complete mitochondrial genome sequences make sense only in very closely related individuals. Recombination activities involving repeated sequences may generate subgenomic forms and extensive structural variation of angiosperm mitochondrial genomes even within the same species [ 11 , 12 , 14 , 15 , 17 , 19 , 26 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the highly dynamic structure of mitochondrial genomes of angiosperms, alignments of complete mitochondrial genome sequences make sense only in very closely related individuals. Recombination activities involving repeated sequences may generate subgenomic forms and extensive structural variation of angiosperm mitochondrial genomes even within the same species [ 11 , 12 , 14 , 15 , 17 , 19 , 26 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial genome sequences of angiosperms generally have one or more pairs of large nontandem repeats (interspersed repeats) that can act as sites for inter- and intramolecular recombination, leading to multiple alternative arrangements (isoforms; including subgenomic forms) within a species [ 19 ]. Although plant mitochondrial genomes are often assembled and displayed as circular maps, plant mitochondrial DNA (mtDNA) does most likely not exist as one large circular DNA molecule but mostly as a complex and dynamic collection of linear DNA with combinations of smaller circular and branched DNA molecules [ 12 , 14 , 15 , 17 , 19 , 26 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mitochondrial genome of the CMS-S-type onion variety “Momiji-3” was characterized which have a multi-chromosomal structure resulting from recombination events. Examination of transcript data revealed RNA editing at 635 positions, and a candidate gene for CMS in “Momiji-3” was also found to be orf725 ( Tsujimura et al, 2019 ) . Similarly, Kim, Yang & Kim (2019) compared the mitochondrial genome of two recently diverged cytoplasms—male-fertile and male-sterile CMS-T-like cytoplasms and obtained almost identical sequences.…”
Section: Survey Methodologymentioning
confidence: 99%
“…Unlike in eukaryotic genomes, splice sites were clustered at genomic loci (Figure 4, Supplemental Table S3) and almost 50% of splice sites were within coding regions. Recently (Tsujimura et al, 2018) reported on the three mitochondrial chromosomes of Allium cepa (onion) CMS line Momiji-3. However, unlike in sugarcane the mitochondrial sub-circles of onion can combine into a master circle through recombination at long repeats.…”
Section: Transcriptomic Read Mappingmentioning
confidence: 99%
“…Indeed, though the plant mitochondrial genome structure is often portrayed as a circle, micrograph studies reveal that the true physical structure of the mitogenome appears to be a variety of circles, linear molecules, and complex branching structures (Backert, Nielsen & Börner1997;Backert & Börner 2000). While many plant species appear have a single master circle representation of their mitochondrial genome, others are composed of more than a hundred circular chromosomes (Sloan et al, 2012) and two independent chromosomes as in Allium cepa (Tsujimura et al, 2018). The precise mechanism of how plant mitochondria replicate and maintain their DNA is not yet fully understood (Cupp & Nielsen 2014) but it is hypothesized that recombination-dependent replication plays a role, giving a functional role to the repeat sequences often observed in mitochondria (Gualberto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%